Hilliella rhombea (Brassicaceae), a new species from eastern China - Ma, Dan-Dan; Xie, Wen-Yuan; Chen, Zheng-Hai; Xia, Guo-Hua (Phytotaxa, 2018)
Hilliella rhombea, a new species of Brassicaceae from Zhejiang, eastern China is described and illustrated. It is similar to Hilliella fumarioides (Dunn) Y. Z. Zhao, but can be distinguished from the latter fruit rhombic, valves membranous, glabrous or sparsely papillate.